The long-term health consequences of genocide: developing GESQUQ - a genocide studies checklist - Jutta Lindert; Ichiro Kawachi; Haim Y. Knobler; Moshe Z. Abramowitz; Sandro Galea; Bayard Roberts; Richard Mollica; Martin McKee (Conflict and Health, 2019)
Abstract Background Genocide is an atrocity that seeks to destroy whole populations, leaving empty countries, empty spaces and empty memories, but also a large health burden among survivors is enormous. We propose a genocide reporting checklist to encourage consistent high quality in studies designed to provide robust and reliable data on the long term impact of genocide. Methods An interdisciplinary (Public Health, epidemiology, psychiatry, medicine, sociology, genocide studies) and international working committee of experts from Germany, Israel, the United States, and the United Kingdom used an iterative consensus process to develop a genocide studies checklist for studies of the long term health consequences. Results We created a list of eight domains (A Ethical approval, B External validity, C Misclassification, D Study design, E Confounder, F Data collection, G Withdrawal) with 1–3 specific items (total 17). Conclusion The genocide studies checklist is easy to use for authors, journal editors, peer reviewers, and others involved in documenting the health consequences of genocide.